CULTURAL PAREMIOLOGICAL EXPRESSIONS RELATED TO TIME IN UZBEK AND ENGLISH LANGUAGES RELATIONSHIPS ABOUT THEIR IMPORTANCE IN REFLECTING CHANGE (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The proverb, which is considered one of the ancient examples of folklore, is different .It is different from other genres due to its short, concise, figurative and deep content stands out. The ancient and rich spirituality of each nation through proverbs appears. Proverbs are extremely rich and diverse in terms of subject matter can be used literally or figuratively. For proverbs as an object, persons, things, and at the same time, animals are taken. The proverbs are mainly didactic in nature and are written by Bahadir Sarimsakov stated that "proverbs can also be used figuratively has This feature defines the thematic scope of proverbs, the level of application expands".